The Importance of Lake Emergent Aquatic Vegetation for Estimating Arctic‐Boreal Methane Emissions. Issue 6 (20th June 2022) - Kyzivat, Ethan D.; Smith, Laurence C.; Garcia‐Tigreros, Fenix; Huang, Chang; Wang, Chao; Langhorst, Theodore; Fayne, Jessica V.; Harlan, Merritt E.; Ishitsuka, Yuta; Feng, Dongmei; Dolan, Wayana; Pitcher, Lincoln H; et al.
Abstract: Areas of lakes that support emergent aquatic vegetation emit disproportionately more methane than open water but are under‐represented in upscaled estimates of lake greenhouse gas emissions. These shallow areas are typically less than ∼1.5 m deep and can be detected with synthetic aperture radar (SAR). To assess the importance of lake emergent vegetation (LEV) zones to landscape‐scale methane emissions, we combine airborne SAR mapping with field measurements of vegetated and open‐water methane flux. First, we use Uninhabited Aerial Vehicle SAR data from the NASA Arctic‐Boreal Vulnerability Experiment to map LEV in 4, 572 lakes across four Arctic‐boreal study areas and find it comprises ∼16% of lake area, exceeding previous estimates, and exhibiting strong regional differences (averaging 59 [50–68]%, 22 [20–25]%, 1.0 [0.8–1.2]%, and 7.0 [5.0–12]% of lake areas in the Peace‐Athabasca Delta, Yukon Flats, and northern and southern Canadian Shield, respectively). Next, we account for these vegetated areas through a simple upscaling exercise using paired methane fluxes from regions of open water and LEV. After excluding vegetated areas that could be accounted for as wetlands, we find that inclusion of LEV increases overall lake emissions by 21 [18–25]% relative to estimates that do not differentiate lake zones. While LEV zones are proportionately greater in small lakes, this relationship is weak and varies regionally, underscoring the need for methane‐relevant remote sensing measurements of lake zones and a consistent criterion for distinguishing wetlands. Finally, Arctic‐boreal lake methane upscaling estimates can be improved with more measurements from all lake zones. Plain Language Summary: Lakes are one of the largest natural sources of the greenhouse gas methane and are especially common in high latitudes. Shallow, near‐shore areas of lakes supporting emergent aquatic vegetation emit disproportionately more methane than open water areas but are under‐represented in broad‐scale estimates of lake greenhouse gas emissions. While lake depths are difficult to map from remote sensing, emergent vegetation, which typically grows in water less than ∼1.5 m deep, can be detected via radar remote sensing. To assess the importance of these areas to landscape‐scale methane emissions, we combine airborne radar mapping with field measurements of vegetated and open‐water methane emissions. Zones of emergent vegetation vary regionally and comprise ∼16% of lake area on average. A simple estimate that accounts for both open water and emergent vegetation methane emissions results in 21% increased overall lake methane emissions estimates. Emergent aquatic vegetation coverage has only a weak relationship with lake size, making it hard to predict. Therefore, to better estimate broad‐scale methane emissions, we suggest using remote sensing to create lake vegetation distribution maps and measuring methane emissions from both vegetated and open water zones within lakes. Key Points: We provide a first quantification of emergent vegetation area across 4, 572 lakes in four Arctic‐boreal study areas using airborne mapping Lake emergent vegetation coverage varies regionally from 1 to 59% of lake area and seasonally to a lesser degree Accounting for this coverage could increase Arctic‐boreal lake methane upscaling estimates by +21%